Topical Sucralfate Versus Hydrocortisone Cream In The Management Of Diaper Dermatitis : A Randomized, Doubleblind Clinical Trial - Iraji Fariba; Kiyani Asadolah; Rezazadeh Marzieh (Wolters Kluwer Medknow Publications, 2004)
Topical corticosteroids are currently used for treatment of diaper dermatitis. Previous studies have shown the efficacy of sucralfate in the treatment of diaper dermatitis and contact dermatitis in peri-stomal areas. To evaluate the efficacy of topical sucralfate in comparison with hydrocortisone cream in the treatment of diaper dermatitis, the present study was under taken. In a double â€"blind randomized clinical trial, 64 patients with diaper dermatitis were treated with sucralfate cream 4% or hydrocortisone cream randomly. The duration of the treatment wad 8 weeks and the patients were evaluated every two weeks until complete healing. The results were evaluated by chi-square test. Complete healing (more than 50% improvement) occurred in 90.6% and partial healing (20-25% improvement) in rest of the patients in each group (p>0.05). Topical sucralfate is an effective, cheap therapeutic intervention for diaper dermatitis. Which has equal efficacy with topical hydrocortisone cream.